Assessment of Knowledge and Attitudes to Preserve Oral Health among Older People Aged 60+ in FYROM - Šapurić M.; Tozja F. (Balkan Stomatological Society, 2015)
Introduction. In the last decade, the impact of oral health on overall health status in the elderly has attracted considerable attention. Elderly people are often not aware that oral diseases and tooth loss can be prevented. Oral health behaviour involves acquisition of individual habits for preservation and maintenance of oral health, such as regular brushing and brushing teeth, using fluoride-rich toothpastes and dental floss, reducing sugar in the diet and habit of regular visits to the dentist. The aim of this research was to assess knowledge and attitude toward maintenance and preservation of oral health in people over 60 years in FYROM.